Taking Stock of Trade Policy Uncertainty : Evidence from China’s Pre-WTO Accession - Alessandria, George; Khan, Shafaat Yar; Khederlarian, Armen (World Bank, Washington, DC, 2021)
This paper studies the effects on international trade from the annual tariff uncertainty about China’s Most Favored Nation (MFN) status renewal in the United States prior to joining the World Trade Organization. The paper makes four main findings. First, in monthly data trade increases significantly in anticipation of uncertain future increases in tariffs and falls upon renewal. Second, the probability of a tariff increase was perceived to be relatively small, with an average annual probability of non-renewal of about 4.5 percent. Third, what matters more is the expected future tariff rather than the uncertainty around it. These effects are identified using within-year variation in the risk of trade policy changes around the renewal vote and trade flows. An (s,S) inventory model generates this behavior and that variation in the strength of the stockpiling in advance of the vote is increasing in the storability of goods. Fourth, the costs associated with within-year trade policy induced stockpiling reduce entrants’ incentive to operate in a market with tariff uncertainty. The results explain why trade may hold up in advance of a prospective policy change, such as Brexit or the US-China escalating tariff war of 2018-19, but may fall sharply even if expected tariff increases do not materialize.